Nutritional effect of the chemical silage of fish by-products in broiler (Gallus domesticuset al.) feeding - Garcés, Yeny; Valencia, N. F.; Hoyos, J. L.; Gómez, J. A. (Cuban Journal of Agricultural Science, 2016)
The present study was aimed at assessing the nutritional effect of including chemical silage of rainbow trout (Oncorhynchus mikiss) viscera (0, 10, 20 and 30 %) in broiler chick (Gallus domesticuset al.) diets. A completely randomized design was used and the productive and economical parameters were determined. There were significant differences (P < 0.05) in feed consumption, live weight gain, feed conversion index, mortality, carcass yield, economic conversion index and economic profitability index. The best results were obtained in diets including 10 and 20 % silage. Results demonstrated that the chemical silage had a high nutritional value constituting a protein and alternative energy source for broiler feeding.Key words: viscera, productive parameters, growth, alternative feeding